Quillbot As An AI-powered English Writing Assistant: An Alternative For Students to Write English - Amanda Amanda; Elsa Muliani Sukma; Nursyahrina Lubis; Utami Dewi (Jurnal Pendidikan dan Sastra Inggris, 2023)
Quillbot is one of the modern era technologies that many students use in learning, it is also one of the online applications to improve writing. Quillbot can help students find writing errors such as punctuation and grammar and others. The purpose of this article is to find out students' perceptions of the use of quillbot as an alternative for students in writing English. This study uses a quantitative method, to find how the use of quillbot in helping English Foreign Language (EFL) to write English. data was collected through questionnaires and interviews that have been calculated and analyzed. The results show that students have a lot of positive perceptions of the use of quillbot in improving writing, as well as found advantages in quillbot that are very helpful to students. With this paper, students are expected to be able to apply it in learning activities related to English writing thus that the resulting writing becomes better.